The use features of diff erent endodontics methods in the megapolis departmental dental clinics (Эндодонтия Today)
The paper presents the results of a clinical study carried out because of a departmental medical organization Megapolus. Based on the study of primary medical documents (PMD), 183 people (144 (78,69%) men and 39 (21,31%) women) aged 18 to 55 years, who were treated in the department of restorative dentistry, examine the structure of treatment deep caries, pulpitis and periodontitis. Regarding the treatment of deep caries received 16 people, including 12 (75%) men and 4 (25%) women. Endodontic treatment took place on the pulpit 167 (132 (79.04%) men and 35 (20.96%) women), about periodontitis - 83 people, including (73 (87.95%) men and 10 (12.05%) of the women). The analysis used by physicians treatment of deep caries, pulpitis and periodontitis, and their frequency, as well as their assessment of a departmental standard endodontic treatment.